Prehospital stroke management in the thrombectomy era. Issue 7 (July 2020) - Fassbender, Klaus; Walter, Silke; Grunwald, Iris Q; Merzou, Fatma; Mathur, Shrey; Lesmeister, Martin; Liu, Yang; Bertsch, Thomas; Grotta, James C
Summary: Acute stroke management has been revolutionised by evidence of the effectiveness of thrombectomy. Because time is brain in stroke care, the speed with which a patient with large vessel occlusion is transferred to a thrombectomy-capable centre determines outcome. Therefore, each link in the stroke rescue chain, starting with symptom onset and ending with recanalisation, should be streamlined. However, in contrast to inhospital delays, prehospital delays are unchanged despite substantial efforts in quality improvement. Furthermore, thrombectomy is offered by only a few, usually distant, specialised centres and not by the many other, usually nearer, hospitals. To take maximum advantage of the first so-called golden hours after stroke, and because of the difficulty of on-scene triage decision making with respect to the target hospital offering the required level of care, the focus of stroke research has shifted to the prehospital setting. Current research focuses on the effects of public education, implementation of protocols for emergency medical services for streamlining clinical investigations and accurate triage, use of preclinical scales for stroke recognition, and deployment of novel technical solutions such as smartphone applications, telemedicine, and mobile stroke units.